Rancang Bangun Aplikasi Catatan Ku Berbasis Android - Hamka, Muhammad; Purnama, Iwan (Jurnal Gemilang Informatika (GIT), 2024)
Along with the development of a more advanced era, the world of information and digital data processing is becoming more automated. However, there are still many data records processed using manual processes, such as in schools, government/private institutions, and inefficient companies. The weaknesses of the author plan to make notes that use computerized data that supports practical information and is more efficient and easy to apply. Technological developments in smartphones are very beneficial for everyday life, and certainly make daily tasks easier so that you can make time more efficient. Apart from that, the convenience of using smartphones also influences various activities such as filling in notes which require making notes in a book. With the My Notes application, it makes it easier for users to make new notes without having to take a book and it is much easier to take notes anywhere via smartphone.